Word Power Made Easy : The Most Effective Vocabulary Builder in the English Language - Lewis, Norman (New Delhi Bloomsbury - GOYLSaab, 1994)
Offers a step-by-step program for increasing knowledge and mastery of English by developing the vocabulary skills necessary in effective reading, writing, and speech communication
Including Latest Word - List
Keywords: Language : Vocabulary / Etymology - English